Nastanak frazema putem semantičkih figura - Stevović, Irena (Slavia Centralis, 2020)
Creation of idioms from semantic figures In this paper, we present idioms in the Montenegrin language from the aspect of semantics, and investigate the processes of their creation, i. e. processes of semantic nature. We highlight questions concerning those idioms whose basic form is a non-idiomatic syntagm that is transposed into the realm of the idiomatic by means of semantic figures. By analysing the idioms in a narrower sense, we try to contribute to the illumination of semantic characteristics of idioms, i. e. the role of semantic figures in the process of creation of these linguistic units.